DNA Mutation in CVPDr DNA Fragment of Bali Citrus - Diah Yuniti, Gusti Ayu; Wirawan, Gede Putu; Wijaya, Nyoman; Sritamin, Made (International Journal of Psychosocial Rehabilitation, 2020)
The CVPDr DNA fragment was identified previously and found in some citrus plants in Bali. This DNA fragment was said to be a resistant factor against citrus vein phloem degeneration (CVPD), or citrus greening, or also called huanglongbing disease. However, the CVPDr DNA fragment also found in some other citrus plants which susceptible to CVPD disease. In this study we analyzed the DNA sequence of CVPDr DNA fragments from 13 citrus plants. The results of this study found some mutations in some citrus plants comparing to the CVPDr DNA fragments of Triphacia trifolia which considered to be resistant to the disease. The mutation included deletion, insertion, transvertion, and transition on the DNA sequences of each sample. These mutations may affect the character of CVPDr DNA fragment and resulted in susceptible to the disease. The dendogram derived from this sequence analysis showed the genetic distance/similarity of each citrus plants to T. trifolia. The citrus plants which cluster near T. trifolia showed rather tolerance to CVPD disease.